SWOT ANALYSIS OF SHARIA BANKING FINANCIAL TECHNOLOGY (FINTECH) AT PT. SUMUT BANK SHARIA BRANCH PADANGSIDIMPUAN: ANALISIS SWOT FINANCIAL TECHNOLOGY (FINTECH) PERBANKAN SYARIAH PADA PT. BANK SUMUT CABANG SYARIAH PADANGSIDIMPUAN - Wulandari, Widia; Rezqi Vitria, Indah; Adela, Dinda (LPPM UPMI, 2023)
The theory used in this study is fintech, the legal basis of fintech, types of fintech, financial Technology (Fintech) of Islamic banking, the benefits of fintech, the role and objectives of fintech, Islamic banking, the legal basis of Islamic banking, the principles of Islamic banking, the function of Islamic banking and the objective role of Islamic banking. Freddy Rangkuti's theory related to SWOT analysis (Strength, Weakness, Opportunity, Threat). This research is a qualitative research with a descriptive approach. Data collection was carried out using interviews and documentation. The data source used is primary data, namely information sourced from interviews with customer service and 5 customers at PT. Bank Sumut Padangsidimpuan Sharia Branch, while secondary sources are data obtained from documentation or literature to complement primary data. Based on the results of the research that has been done, it can be seen that the SWOT Financial Technology (Fintech) analysis is related to the mobile banking of Bank Sumut Padangsidimpuan Syariah Branch, namely strength, ease of making transactions anywhere and anytime, time efficiency so that customers don't bother coming to Bank Sumut. Direct Sharia branch.